A Guide to the Singapore Presidency - SMU Apolitical (Institutional Knowledge at Singapore Management University, 2017)
Singapore adopted the Westminster Parliamentary system of government from the United Kingdom. Under this system, the head of state and head of government are distinct roles that are held by different people. The head of state of Singapore is the President, and in the United Kingdom it is the monarch who holds that responsibility. The head of government in both countries is the Prime Minister. Before 1991, the President was “elected” (essentially appointed) by Parliament. The role of the President was entirely ceremonial. Singapore’s first President, Yusof Ishak, who was also the last Yang di-Pertuan Negara, interacted with various communities frequently to promote a sense of togetherness and communal trust. This was especially important because following Singapore’s separation from Malaysia, there was much uncertainty and disheartenment among the people. In 1991, the Singapore Constitution was amended to make the Presidency an elected position.